2023
DOI: 10.1039/d2fo02716j
|View full text |Cite
|
Sign up to set email alerts
|

Kaempferol prevents acetaminophen-induced liver injury by suppressing hepatocyte ferroptosis via Nrf2 pathway activation

Abstract: Acetaminophen (APAP)-induced liver injury (AILI) has become a growing public health problem. Ferroptosis, an iron-dependent form of cell death associated with lipid peroxide accumulation, has been recently implicated in AILI....

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 76 publications
(107 reference statements)
2
22
0
Order By: Relevance
“…It is well-known that ROS serve as another pivotal index to evaluate ferroptosis. 43 So, in this study, we also checked the effect of rutin on the ROS level, and found that the ROS levels were increased in the PASMCs under hypoxia, but rutin suppressed the overproduction of ROS, as shown in Fig. 2L.…”
Section: Resultsmentioning
confidence: 65%
“…It is well-known that ROS serve as another pivotal index to evaluate ferroptosis. 43 So, in this study, we also checked the effect of rutin on the ROS level, and found that the ROS levels were increased in the PASMCs under hypoxia, but rutin suppressed the overproduction of ROS, as shown in Fig. 2L.…”
Section: Resultsmentioning
confidence: 65%
“…This indicates that KF suppresses ferroptosis via the Nrf2/SLC7A11/GPX4 signaling pathway . Additionally, KF has been found to reverse liver injury and iron overload induced by acetaminophen through its effects on Nrf2 …”
Section: Targeting Ferroptotic For Treatment Of Neurodegenerative Dis...mentioning
confidence: 87%
“…76 Additionally, KF has been found to reverse liver injury and iron overload induced by acetaminophen through its effects on Nrf2. 130 Puerarin is an active ingredient found in Pueraria, with several pharmacological activities, such as being anti-inflammatory and an . 131 Recent studies have shown that puerarin protects against myocardium injury via the TLR (Toll-like receptor)4/NF-κB/ JNK signaling pathway.…”
Section: Natural Ferroptosis Regulatory Compoundsmentioning
confidence: 99%
“…38 The anti-inflammatory pathways of kaempferol include inhibition of NF-κB binding activity, inhibition of IL-6, IL-1β, IL-18, and TNF-α release by myeloid activators, and inhibition of Toll-like receptors by increasing nRF2 regulatory gene mRNA and protein expression. [39][40][41] Luteolin is derived from epimedium, and Chen et al 42 showed that luteolin effectively blocked the activation of NF-κB and AP-1 and inhibited the gene expression of TNF-a, IL-6, inducible nitric oxide synthase (iNOS) and cyclooxygenase-2 to achieve the F I G U R E 8 KEGG enrichment analysis of MBYF core targets for COPD.…”
Section: Discussionmentioning
confidence: 99%
“…Quercetin has also been shown to inhibit the production of inflammatory cytokines and chemokines such as IL‐1β and TNF‐a via mitogen‐activated protein kinase (MAPK) and nuclear factor‐kappa B (NF‐κB) signaling pathways in cells 38 . The anti‐inflammatory pathways of kaempferol include inhibition of NF‐κB binding activity, inhibition of IL‐6, IL‐1β, IL‐18, and TNF‐α release by myeloid activators, and inhibition of Toll‐like receptors by increasing nRF2 regulatory gene mRNA and protein expression 39–41 . Luteolin is derived from epimedium, and Chen et al 42 showed that luteolin effectively blocked the activation of NF‐κB and AP‐1 and inhibited the gene expression of TNF‐a, IL‐6, inducible nitric oxide synthase (iNOS) and cyclooxygenase‐2 to achieve the effect of treating inflammatory diseases in the lung.…”
Section: Discussionmentioning
confidence: 99%